Analysis of autosomal genes reveals gene–sex interactions and higher total genetic risk in men with systemic lupus erythematosus. Issue 5 (21st November 2011) - Hughes, Travis; Adler, Adam; Merrill, Joan T; Kelly, Jennifer A; Kaufman, Kenneth M; Williams, Adrienne; Langefeld, Carl D; Gilkeson, Gary S; Sanchez, Elena; Martin, Javier; Boackle, Susan A; Stevens, Anne M; et al.
Abstract : Objectives: Systemic lupus erythematosus (SLE) is a sexually dimorphic autoimmune disease which is more common in women, but affected men often experience a more severe disease. The genetic basis of sexual dimorphism in SLE is not clearly defined. A study was undertaken to examine sex-specific genetic effects among SLE susceptibility loci. Methods: A total of 18 autosomal genetic susceptibility loci for SLE were genotyped in a large set of patients with SLE and controls of European descent, consisting of 5932 female and 1495 male samples. Sex-specific genetic association analyses were performed. The sex–gene interaction was further validated using parametric and non-parametric methods. Aggregate differences in sex-specific genetic risk were examined by calculating a cumulative genetic risk score for SLE in each individual and comparing the average genetic risk between male and female patients. Results: A significantly higher cumulative genetic risk for SLE was observed in men than in women. (P=4.52x10-8) A significant sex–gene interaction was seen primarily in the human leucocyte antigen (HLA) region but also in IRF5, whereby men with SLE possess a significantly higher frequency of risk alleles than women. The genetic effect observed in KIAA1542 is specific to women with SLE and does not seem to have a role in men. Conclusions: The data indicate that men require a higher cumulative genetic load than women to develop SLE. These observations suggest that sex bias in autoimmunity could be influenced by autosomal genetic susceptibility loci.